Students’ Experiences Using The Educational Game “Lentera Waktu: Jejak Peradaban” As A Tool For Learning Islamic Cultural History (Ski) - Yenny Aulia Rachman; Fani Nur Aini; Vina Khoirul Latifah; Muhammad Chasanun; Imam Ma’ruf Solihudin (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Abstract The teaching of Islamic Cultural History (ICH) is often perceived as less engaging due to its emphasis on factual and chronological content, highlighting the need for innovative instructional media to enhance student engagement. This study aimed to describe students' learning experiences using the *Lentera Waktu: Jejak Peradaban* educational game developed on the Educaplay platform and to explore their perceptions of its role in supporting their understanding of Islamic Cultural History. A descriptive qualitative approach was employed, involving fifth-grade students at MI Ma'arif Malebo as the research participants. Data were collected through classroom observations during the learning process and interviews with the homeroom teacher. The data were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings revealed that the educational game created a more interactive, enjoyable, and engaging learning environment. Students demonstrated high enthusiasm, actively participated in classroom activities, and showed greater confidence in answering questions and presenting in front of their peers. All students successfully completed the game and answered all questions correctly, indicating that the learning material was effectively understood through the game-based approach. Furthermore, students expressed positive perceptions of the game, stating that it facilitated their understanding of the material, increased their learning motivation, strengthened knowledge retention, and made Islamic Cultural History lessons more enjoyable. Therefore, the *Lentera Waktu: Jejak Peradaban* educational game developed through Educaplay can serve as an effective alternative instructional medium for improving the quality of Islamic Cultural History learning in elementary schools. Keywords: educational game, Islamic Cultural History, Educaplay, learning experience, students' perceptions.